Molecular characterization, polymorphism and expression analysis of swamp eel major histocompatibility complex class II B gene, after infection by Aeromonas hydrophilia - W. Li; 2; W.X. Sun1; J.F. Hu; D.W. Hong; S.L. Chen (Journal of Animal and Plant Sciences, 2014)
Major histocompatibility complex (MHC) class II genes play a crucial role in the immune system of vertebrates. Here we report the cloning of full-length cDNA from the swamp eel (Monopterus albus) MHC class II B (MHC-DAB) gene. We described its genomic structure, molecular polymorphism and expression profiles. The full-length cDNA (Gen Bank accession No.:JQ236680) is 1339 bp, encoding a 249 amino acid peptide. The genomic sequence was identified to be 3066 bp in length, which contained six exons and five introns. Sequence comparison showed that the proposed amino acid sequence shared between 26.4 and 74.7% identity with other species. Thirty seven distinct alleles were isolated from sixty individuals. There were between two and five alleles per individual. The presence of five alleles in an individual suggested that there were at least three MHC IIB loci in the genome. At the protein-binding region dN was significantly greater than dS, providing evidence of strong positive selection among swamp eel sequences. RT-PCR demonstrated high MHC-DAB expression in stomach, spleen, blood cell and liver, moderate expression in brain, skin and kidney, and low or negligible expression in heart, intestine and muscle. Great changes were observed in liver, spleen and intestine after challenged with pathogenic bacteria, Aeromonas hydrophilia.
Keywords: Major histocompatibility complex (MHC); cDNA; genomic structure; polymorphism; swamp eel (Monopterus albus)